Genetic diversity analysis in marigold (Tagetes Spp.) (Bangladesh Journal of Botany, 2025)
The present investigation was carried out to assess the extent of genetic variability, heritability, genetic advances and divergence using 16 marigold (Tagetes spp.) genotypes with eighteen characters. Moderate to high genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were recorded for almost all the characters under study emphasizing the existence of variation in the population. All the characters showed higher heritability along with higher/moderate GCV and genetic advances indicating that most likely the heritability was due to additive gene effects and the genotypes under study were highly diverse and of great potential with regard to these characters, and therefore, these were more reliable for effective phenotypic selection. The inter-cluster average D2 value was maximum between cluster I and IV followed by between cluster II and IV. However, minimum inter-cluster distance was obtained between cluster II and cluster V indicated that genotypes of cluster II and V are very close to each other. The clustering pattern showed that genotypes of different geographical areas were clubbed in one group and also the genotypes of same geographical areas were grouped into same cluster as well as in different clusters indicating formal relationship between geographical diversity and genetic diversity.Bangladesh J. Bot. 54(2): 211-219, 2025 (June)